PERANG SIBER di ERA KONEKTIVITAS TINGGI: KONVERGENSI JARINGAN KOMUNIKASI DATA dan KONFLIK DIGITAL - Rizky Habibie, Muhammad; Nabila, Putri; Zakiya Faizza, Aufa; Lil Alamin Arrasyid, Rakhmatan; Sulistyani, Anjar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the relationship between data communication network convergence and the escalation of global cyber warfare in the high-connectivity era. The integration of Internet of Things (IoT), cloud computing, edge computing, and 5G networks has created efficient yet vulnerable communication ecosystems. Using a qualitative comparative case study on SolarWinds (2020), Colonial Pipeline (2021), and Ukraine’s energy cyberattacks (2022–2024), the study finds that technological convergence expands cross-domain vulnerabilities (IT–OT–Cloud–Edge), triggers cascading impacts on critical systems, and accelerates the shift toward integrated digital warfare. The research introduces the Strategic Convergence Theory, emphasizing the need for zero-trust architectures, cross-sector cyber deterrence policies, and adaptive resilience-based governance to strengthen global cybersecurity.